Flipped classroom in physiology education: where are we and where are we heading? - Jing Liu; Jing Liu; Zheng Wu; Zheng Wu; Yang-Zheng Lan; Yang-Zheng Lan; Wen-Jia Chen; Wen-Jia Chen; Bing-Xuan Wu; Wen-Tian Chen; Hua-Tao Wu (Frontiers in Education)
Flipped classroom (FC) is considered a student-centered teaching method that improves internal active learning of students and their acquisition of knowledge and skills. Among many medical majors, physiology is quite important as a bridge between basic and clinical principles. However, the complex and abstract nature of physiology causes learning stress to students. As the use of FC is widespread across various majors and principles with beneficial effects, analyzing its application in physiology is important to comprehensively evaluate its effectiveness and advantages, as well as disadvantages, and to improve the specific procedures of FC conduction. This article reviews the research on FC utilization in physiology education and summarizes its effectiveness and feedback from both educators and learners, serving as a guideline to facilitate and promote the development of FC in physiology education.